Numerical Investigation of Seismic Performance of Steel Concentrically Braced Frames Subjected to Critical Consecutive Earthquakes - Sahar Rouzrokh; Elham Rajabi; Gholamreza Ghodrati Amiri (Journal of Rehabilitation in Civil Engineering)
This paper evaluates the effect of critical successive-shocks on the seismic performance of steel concentrically braced frames (CBFs) for significant structural design parameters such as behavior factor(R), displacement amplification factor (Cd), maximum drift and damage index (DI). For this purpose, three CBFs with 3,7and 11-stories are investigated using IDA, nonlinear dynamic analysis (NDA) under recorded critical seismic scenarios with/without successive-shocks and pushover. Results show that the average of R-factors has a 14% reduction rate under successive earthquakes compared with that of individual earthquakes. While Cd is not significantly affected by successive shocks, the occurrence of secondary-shocks increased DI by 1.8 times. In severer cases, the maximum drift is increased by up to 2 times. Finally, the sensitivity of seismic demand parameters to periods, PGA of first and second-shock is also evaluated by training an ideal ANN and proposing the empirical equations. Moreover, the effect of artificial successive shocks is examined on the seismic performance of CBFs. Despite what is necessitated in the seismic design codes, considering a constant value as R-factor for the whole steel structure cannot lead to the proper design of these structures especially under successive scenarios. Also, the use of artificial consecutive earthquakes can cause the inadequate assessment of seismic performance.